A hyperelastic-damage model to study the anisotropic mechanical behavior of coral-hydrogel bio-composite. (February 2022) - Eghbali, R.; Narooei, K.
Abstract: In this research, a hyperelastic strain energy function was developed to investigate the anisotropic mechanical behavior of a soft bio-composite containing the coral collagen fibers and alginate hydrogel matrix. This hyperelastic function considers the matrix isotropic response, anisotropic behavior of soft crimpled fibers, and matrix-fiber interaction. The material parameters of the model were assumed as a function of the volume fraction of fibers to consider the fiber content. The published experimental data of matrix and bio-composites with different volume fractions of fibers in different directions were used to find the material parameters. A damage model was developed to take into account the damage of matrix, fibers, and fiber-matrix interaction. Results showed that the interaction contribution increases by increasing the volume fraction of fibers due to the crosslinks between the matrix and fibers. Moreover, by exceeding the fibers volume fraction from 20%, the anisotropic stiffening dominates the interaction stiffening in the longitudinal test owing to the load-bearing of soft fibers. Simulation results exhibited that cross-plied bio-composites show more uniform deformations than angle-plied bio-composites. Moreover, the damage results showed that the matrix plays a significant role in the failure of bio-composites.